2022
DOI: 10.3389/fnins.2022.952329
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 24-h acute total sleep deprivation on physiological coupling in healthy young adults

Abstract: Sleep deprivation is associated with dysregulation of the autonomic nervous system, adverse cardiovascular events, cognitive and complex motor performance impairment. Less is known about the effects of acute total sleep deprivation (ATSD) on physiological coupling. We aimed to determine the effects of 24-h ATSD on the physiological coupling between complex subsystems by evaluating the cardiorespiratory, cardiovascular and cortico-cardiac interactions. This study enrolled 38 young healthy participants aged 23.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 47 publications
(76 reference statements)
0
7
1
Order By: Relevance
“…In both groups, the U-shaped pattern of MCRT was confirmed, which is in agreement with most of the previous data [ 15 , 16 , 17 , 18 ]. The lack of differences in MCRT and the shortest MCRT between groups is in contrast to what would be expected based on the results of studies on SD alone, which almost unanimously report the detrimental effect of the lack of sleep on psychomotor performance and other aspects of the cognitive functions as well [ 2 , 3 , 4 , 5 , 19 ]. This could be explained by what has been already found at rest, namely the higher arousal induced by prolonged exercise had balanced its decrease produced by the lack of sleep.…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…In both groups, the U-shaped pattern of MCRT was confirmed, which is in agreement with most of the previous data [ 15 , 16 , 17 , 18 ]. The lack of differences in MCRT and the shortest MCRT between groups is in contrast to what would be expected based on the results of studies on SD alone, which almost unanimously report the detrimental effect of the lack of sleep on psychomotor performance and other aspects of the cognitive functions as well [ 2 , 3 , 4 , 5 , 19 ]. This could be explained by what has been already found at rest, namely the higher arousal induced by prolonged exercise had balanced its decrease produced by the lack of sleep.…”
Section: Discussioncontrasting
confidence: 63%
“…The novel aspect of the present study reveals the psychomotor performance measured during exercise in subjects submitted to 30 h of sleep deprivation combined with moderate intensity prolonged exercise (SDE). Interestingly, psychomotor performance measured at rest in the SDE trial was improved, most probably because the additional stimulation induced by prolonged exercise annihilated the usually observed detrimental effect of sleep deprivation [ 2 , 3 , 4 , 5 , 19 ]. Several factors influenced by exercise also affect the brain and might have led to such a result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observed changes resulted in an increase in the left ventricular ejection time (LVET) and pre-ejection period (PEP). In the current literature, changes in cardiac function during sleep fragmentation or even acute sleep deprivation are less well-defined [21]. The authors' previous study has shown that sleep fragmentation affects haemodynamics, notably stroke index more than sleep deprivation [22].…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] In particular, the mean nocturnal baseline impedance (MNBI) and the postreflux swallow-induced peristaltic wave index Medicine (PSPWI) are important in the diagnosis and evaluation of GERD, but their association with valve classification has not been clarified. [7] To fill this knowledge gap, this study aimed to investigate the relationship between endoscopic gastroesophageal valve grading and MNBI and PSPWI in patients with GERD. We collected the clinical data of 120 patients with GERD and divided them into 5 groups according to the severity of endoscopic gastroesophageal valve grading.…”
Section: Introductionmentioning
confidence: 99%